Early Intervention with Impedance-guided Heart Failure Management Improves Long-term Outcome: insights From the IMPEDANCE-HF Trial. (3rd October 2022) - Kleiner Shochat, M; Fudim, M; Kazatsker, M; Kleiner, I; Weinstein, J M; Panjrath, G; Kobo, O; Roguin, A; Meisel, S
Abstract: Background: Lung-impedance (LI) guided treatment of heart failure (HF) patients was shown to improve clinical outcomes. Objectives: To perform a post-hoc analysis of the IMPEDANCE-HF extended trial in order to explore the mechanism underlying the improved outcome of the LI-guided compared with conventional therapy of HF patients. Methods: The study included 290 HF patients with LVEF ≤45% randomized 1:1 to LI-guided or conventional therapy. The normal LI (NLI), representing the dry lung status, was calculated upon enrollment. The level of pulmonary congestion (LPC) was represented by ΔLIR= [(measured LI/NLI)-1] × 100%. Results: There were 11473 outpatient visits in the LI-guided group and 10245 visits in the control group during follow-up, or 15.5 and 15.9 visits/patient×year, respectively (p=0.74). The LI-guided patients were on average less congested during follow-up than those in the control group (by 20%, p<0.01). Multivariate regression analysis showed that the likelihood of hospitalization for HF [hazard ratio (HR): 0.62, 95% confidence interval (CI): 0.52–0.72, p<0.01) and of all-cause mortality (HR: 0.83, 95% CI: 0.70–0.98, p=0.03] were lower in the LI-guided group than in the control group. In the LI-guided group, diuretic up-titration was 2-fold more frequent and at an earlier timepoint and at a 21% lower LPC (p<0.01). In both groups the diuretic response was more prominent when up-titration was done at a lower LPC (p<0.01). Conclusion: LI-guided diuretic titration prompted earlier, and more frequent diuretic dose increase when the LPC was only beginning to increase and this resulted in a greater decongestive response with better clinical outcomes. Funding Acknowledgement: Type of funding sources: None.